The Description Of Attitude Visit To The Dentist And Caries Status Of Seventh Grade (Aged 12-13 Years Old) Student In SMP Negeri 3, District Cepu, Blora - Cahya Mustika, Annisa; , Drg. Soetomo Nawawi, DPH.Dent,Sp.Perio (2016)
ABSTRACT Dental caries is defined as a disease that attacks the email, cementum, and dentin due to the effect of exposure to the activity of microorganisms in fermented food capable. Visit to the dentist is one of the primer prevention for dental caries. Comprehenssion attitude of visit to dentist for junior high school student will be encouraging the student to visit the dentist in order to avoid dental desease, especially dental caries. This research was descriptive observasional with cross sectional approach. The goal is to describe the attitude of dental visits student aged 12-13 years old in SMP Negeri 3 District of Cepu, Blora. The samples using purposive sampling method, as much as 225 students appropriated inclusion criteria predetermined by the researcher. Retrieving data using a questionnaire to describe the attitude of visit to the dentist and inspection DMF-T in order to know the status of caries students. The research result showed that the biggest precentage of student attitude visit to dentist in seventh grade of SMP Negeri 3, district of Cepu, Blora, is 54,67%, which is included in the medium category. The students belong to low category going to the dentist is classified into 26,92% who are from low social status, 51,28% who are afraid, and who have low motivation in the percentage 61,53%. The students are caregorized into medium category to go to the dentist is elaborated as follows: the low social status students is 4,87%, students are afraid is 16,26%, and students with low motivation is 37,6%. The last one is students belong to high category visiting the dentist can be explained as 0% who are in the low social status, 19,17% who are afraid, and 8,19% who have low motivation. The highest percentage of student visit to the dentist is if just they had been big perforated teeth (40,4%) and as much as 78,8% think the sore tooth to be remove if they make a visit to the dentist. The mean of DMF-T seventh grade students aged 12-13 years in SMP Negeri 3 District of Cepu Blora at 1,062, included in the very low category, it means that each student has the teeth damaged by caries. Keywords: Attitude visit to the dentist, caries status, seventh grade students of SMP Negeri 3 District of Cepu, Blora.